Synergistic effects of proteinaceous pheromone and nitrogen starvation on male gametogenesis in the anisogamous volvocine alga Eudorina - Hiroko Kawai-Toyooka; Makoto Ono; Takashi Hamaji; Hisayoshi Nozaki; Masafumi Hirono (PLoS ONE, 2025)
In volvocine algae, gametogenesis is triggered by different cues depending on the species and their sexual systems. In isogamous unicellular organisms such as Chlamydomonas reinhardtii , which produce gametes of equal size and morphology, nitrogen depletion induces gametogenesis. In contrast, in oogamous multicellular species of the genus Volvox , which produce large, immobile eggs and small motile sperm, male gametogenesis is induced by a sex pheromone secreted by sperm packets (SPs), i.e., bundles of male gametes. Eudorina , an anisogamous multicellular volvocine alga that produces motile gametes of different sizes, is known to form SPs under nitrogen-depleted conditions. Intriguingly, a pheromone-like factor, present in male conditioned medium (CM), has also been implicated in SP formation. To clarify the relative contributions of nitrogen starvation and pheromone signaling, we conducted semi-quantitative analyses of SP induction using synchronously cultured male colonies of Eudorina . When CM was added to male cultures during an early maturation stage, most colonies formed SPs regardless of nitrogen availability. However, when the CM was diluted 100- to 100,000-fold, SP formation was significantly more efficient under nitrogen-depleted conditions than under nitrogen-replete conditions. Notably, SPs never formed without the addition of CM, even in a nitrogen-depleted medium. The SP-inducing activity of the CM was found to markedly decrease with protease treatment. These findings suggest that spermatogenesis in Eudorina is induced by a proteinaceous sex pheromone secreted by male colonies, and that nitrogen depletion, while not essential, enhances this pheromone activity.